Superior agricultural human resource management for the achievement of food security in ngada district east Nusa Tenggara province - Wuli, Rofinus Neto (SEAN Institute, 2024)
Food security is a condition where the food needs of the entire population are met regularly, safely and sustainably. Food security can be achieved through various efforts, one of which is by managing superior agricultural human resources (HR). This research examines superior agricultural human resource management to achieve food security in Indonesia. This study used qualitative research methods. Data collection techniques in this research were carried out using literature study, observation and interviews. The data that has been collected is then analyzed using three stages, namely data reduction, data presentation, and conclusion. The research results show that managing superior agricultural human resources to achieve food security in Ngada Regency is important. Superior management of agricultural human resources can be done through several efforts, namely improving the quality of education and training, increasing motivation and welfare, empowering farmer organizations, and increasing cooperation between parties.